Pengaruh Disiplin Kerja, Stres Kerja dan Motivasi Terhadap Kinerja Driver Studi Kasus Pada CV Kurir-Kuriran di Samarinda - Sabrina Ummu Chultzum (Publikasi Indonesia, 2023)
This research is against the backdrop of researchers' anxiety about the company's productivity that tends to decline. According to the results of studies from several research studies that employee performance is influenced by various factors. Not only work discipline, work stress can also affect the performance of an individual. On the other hand, employee productivity is also influenced by the level of motivation and stress power possessed by each employee. Therefore, this study will examine the influence of work discipline, work stress and motivation on driver performance. This study aims to determine the influence of work discipline, work stress and motivation on driver performance in the Samarinda Courier-Kuriran CV. This research uses a quantifiable approach method. The sample used was 80 drivers. Data collection techniques by distributing questionnaires. The data analysis techniques tested are validity test, reliability, classical assumption test, multiple regression analysis, T test hypothesis test, F test, and coefficient of determination. The results showed that partially work discipline did not have a significant effect on driver performance. Work stress has no significant effect on driver performance. Motivation has a significant effect on driver performance. Simultaneously work discipline, work stress and motivation have a significant effect on driver performance. Thus the researcher recommended to CV Kurir-Kurian to improve the system of work procedures by developing the order system into an application, providing facilities that can reduce the burden on drivers and further increase driver motivation by providing bonuses.